Encephalitis with autoimmune disease in pediatric patients General X Hospital Yogyakarta Indonesia: a case report study - Adi, Giri Susilo; Priliana, Wiwi Kustio; Pratiwi, Etik; Nurzulaekha, Anisa Guntias (International Journal Of Community Medicine And Public Health, 2020)
Encephalitis is an infection of brain parenchymal tissue by various microorganisms. In encephalitis inflammation of brain tissue occurs. The purpose of this case study is to introduce the case of encephalitis and nursing care that occurs in children, especially in the area of Central Java as one area in Indonesia. This is a case study; the case was taken from a case of managed patient in the X central hospital. Patient management is carried out for 3 days. A 7 years old pediatric patient coming from neurology poly. One year before the hospital, the child had a seizure of GTC with a duration of 6 hours, was unconscious and then taken to the general hospital after the seizure the child appeared to be hyperactive and had no eye contact. Six months before being admitted to the hospital, the child was taken to the RSA then blood tested and a positive CMV check was performed. The child is then managed as autoimmune encephalitis. nurses perform nursing care for 7 days. Families understand more about the care process in children with encephalitis, especially in terms of infection problems, growth and development, the risk of falls, and drug management. be at home later.